The polynomial is given to be:
![3x^2+3x^3=6x^4](https://img.qammunity.org/2023/formulas/mathematics/college/9dyx1ly76m80jy1sv9zybszwbzxbbt4joy.png)
We can rewrite the polynomial to be:
![6x^4-3x^3-3x^2=0](https://img.qammunity.org/2023/formulas/mathematics/college/ejh9qp8t8lvipjcspdh9kzff15iaxh7azb.png)
Factor the polynomial using the common factor of each term:
![\begin{gathered} Factor\Rightarrow3x^2 \\ \therefore \\ \Rightarrow3x^2(2x^2-x-1)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3e1agfiix62yojt23su215tgl7gcsaeqp3.png)
Using the Zero Factor Principle, given to be:
![\begin{gathered} If \\ ab=0 \\ \text{then} \\ a=0,b=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v9pj3iaopei7ar0p129q0rdcaz6zgdh66m.png)
Therefore, we have:
![\begin{gathered} 3x^2=0,x^2=(0)/(3)=0,x=\pm\sqrt[]{0} \\ \therefore \\ x=0(mult.2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zxakghopzn5ds34rept5k59mjntv1ghgf7.png)
or
![2x^2-x-1=0](https://img.qammunity.org/2023/formulas/mathematics/college/5ata7y13aunxttx6d7p8hquscxct0i0f4v.png)
Solving using the quadratic formula given to be:
![\begin{gathered} x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a} \\ \text{where} \\ a=2 \\ b=-1 \\ c=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mdrj2rv6acomgvg50td6n4resykcwn433d.png)
Therefore, we have:
![\begin{gathered} x=\frac{-(-1)\pm\sqrt[]{(-1)^2-4*2*(-1)}_{}}{2*2}=\frac{1\pm\sqrt[]{1+8}}{4}=\frac{1\pm\sqrt[]{9}}{4} \\ x=(1+3)/(4)=-(4)/(4)=1 \\ or \\ x=(1-3)/(4)=(-2)/(4)=-(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/699audjbziof2smnl27fv55lefyhn87fh5.png)
Therefore, the solution to the equation is:
![x=0(mult.2),1,-(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/cccqkqrjhzljzr3x0vj3jfd228r8v6ylrw.png)
Comparing our answers with the provided options, we can check for equivalent answers. From the Third Option, we have:
![\begin{gathered} x=\frac{3\pm\sqrt[]{81}}{12}=(3\pm9)/(12) \\ \therefore \\ x=(3+9)/(12)=(12)/(12)=1 \\ or \\ x=(3-9)/(12)=-(6)/(12)=-(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ef1itnui7bjqzlcqj0k1x91uyj2j7el44s.png)
This is equivalent to the answer we got.
Therefore, the correct option is the THIRD OPTION:
![x=0(mult.2),\frac{3\pm\sqrt[]{81}}{12}](https://img.qammunity.org/2023/formulas/mathematics/college/ugqkyn0nalr8miqt5ybyv70bd51liak9ie.png)